Rancang Bangun Aplikasi Sistem Ujian Online Tanry Education Centre Berbasis Web - Paramitha Gunawan; Prya Artha Widjaja (Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2024)
Learning is the result of an interactive process that takes place between educators and students in a learning environment. For students, a learning tool is needed to help them prepare and improve the various types of material that will be studied directly at school. One form of learning facility is tutoring or usually abbreviated as tutoring. Tutoring is an effort provided by guidance teachers in dealing with and solving learning problems experienced by students. Tanry Education Center is a tutoring institution that offers various levels of education, from kindergarten to high school/vocational school. However, Tanry Education Center has so far still used conventional methods in conducting test, so students have to wait a few days to get their exam results due to time constraints and there are times when students cannot know the correct answer to the given questions. To overcome this problem, research was carried out with the aim of developing and building an online exam system application. The purpose of this application is to assist users in measuring the level of understanding of students' material in Tanry Education Center using a Web-based platform. This research will use the Prototype development methodology and be implemented using the PHP programming language utilizing the CodeIgniter 4 framework. A black box approach will be used to carry out application testing, with a focus on evaluating software functionality.